2012
DOI: 10.1016/j.orgel.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-processed polyethylene as a dielectric for low operating voltage organic field effect transistors

Abstract: Graphical abstractHighlights► Vacuum-evaporated polyethylene (PE) is a highly stable and trap-free dielectric. ► PE supports low-hysteresis transport in C60 and pentacene. ► PE additionally allows ambipolar transistor operation of 6,6′-dibromoindigo with balanced mobilities of ∼0.3 cm2/Vs. ► This work shows that high-quality gate dielectrics consisting of polymeric materials can be vacuum-processed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 23 publications
1
47
0
Order By: Relevance
“…spin coating speed and drying conditions for TMSC; vacuum deposition rate and substrate temperature for chlorinated indigo respectively; improved deposition of contact electrodes by finding the optimum deposition rate for a reduced contact resistance) may lead to well‐balanced n‐ and p‐channels of the individual transistors. This fact may improve the inverter parameters dramatically, as was shown already with other H‐bonded molecules tyrian purple, indigo and quinacridone .…”
Section: Discussionsupporting
confidence: 56%
“…spin coating speed and drying conditions for TMSC; vacuum deposition rate and substrate temperature for chlorinated indigo respectively; improved deposition of contact electrodes by finding the optimum deposition rate for a reduced contact resistance) may lead to well‐balanced n‐ and p‐channels of the individual transistors. This fact may improve the inverter parameters dramatically, as was shown already with other H‐bonded molecules tyrian purple, indigo and quinacridone .…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, the indigoid-based nanodevices exhibited ambipolar operation with the electron ( μ e ) and hole ( μ h ) mobilities from 10 −2 to 0.2 cm 2 (V × s) −1 . In a more recent study, higher mobilities in Tyrian purple were also reported with the μ e and μ h values of 0.4 cm 2 (V × s) −1 [31]. However, the analyzed SET nanodevices are different from any conventional OFET, which only controls the charge density between the electrodes but on the single-electron transport through the energy modifications of molecular orbitals [32, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Anodization of Aluminum Gate Electrode : Al 2 O 3 dielectric layer was grown electrochemically on a vacuum‐evaporated aluminum gate electrode, using a method reported originally by Majewski et al and have been used extensively by several research groups . 60 nm aluminum gate electrodes were evaporated thermally on a 1.5 × 1.5 cm glass slide using a thermal evaporator, at a typical pressure of ≈5 × 10 −6 mbar and a rate of ≈0.5 nm s −1 .…”
Section: Methodsmentioning
confidence: 99%